Penguatan Nilai Karakter melalui Pembelajaran Pendidikan Agama Islam Berkualitas di SMP Muhammadiyah 8 Surakarta - Muchasin, Fiki Vendi; Subando, Joko (TSAQOFAH, 2026)
Strengthening character values is one of the main objectives of national education that must be systematically internalized through the learning process, in which Islamic Religious Education (PAI) plays a strategic role in shaping students’ religious and social character. This study aimed to describe and analyze the planning, implementation, and evaluation of quality PAI learning in strengthening students’ character values at SMP Muhammadiyah 8 Surakarta in the 2025/2026 academic year. The research employed a qualitative approach with a descriptive design, using in-depth interviews, classroom observations, and documentation studies as data collection techniques. Data were analyzed using the interactive Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings show that character strengthening is consistently integrated into lesson planning, into the implementation of learning that emphasizes role modeling and habituation of values, and into evaluation that covers cognitive, affective, and behavioral aspects. Quality PAI learning that is carefully designed and implemented is shown to contribute positively to the formation of students’ religious character, discipline, responsibility, and social concern.